Acceptance and attitudes of healthcare staff towards the introduction of clinical pharmacy service: a descriptive cross-sectional study from a tertiary care hospital in Sri Lanka. Issue 1 (December 2017) - Shanika, Lelwala; Wijekoon, Chandrani; Jayamanne, Shaluka; Coombes, Judith; Coombes, Ian; Mamunuwa, Nilani; Dawson, Andrew; De Silva, Hithanadura
Abstract Background Multidisciplinary patient management including a clinical pharmacist shows an improvement in patient quality use of medicine. Implementation of a clinical pharmacy service represents a significant novel change in practice in Sri Lanka. Although attitudes of doctors and nurses are an important determinant of successful implementation, there is no Sri Lankan data about staff attitudes to such changes in clinical practice. This study determines the level of acceptance and attitudes of doctors and nurses towards the introduction of a ward-based clinical pharmacy service in Sri Lanka. Methods This is a descriptive cross-sectional sub-study which determines the acceptance and attitudes of healthcare staff about the introduction of a clinical pharmacy service to a tertiary care hospital in Sri Lanka. The level of acceptance of pharmacist's recommendations regarding drug-related problems (DRPs) was measured. Data regarding attitudes were collected through a pre-tested self-administered questionnaires distributed to doctors (baseline, N =13, post-intervention period, N = 12) and nurses (12) worked in professorial medical unit at baseline and post-intervention period. Results A total of 274 (272 to doctors and 2 to nurses) recommendations regarding DRPs were made. Eighty three percent (225/272) and 100% (2/2) of the recommendations were accepted by doctors and nurses, respectively. The rate of implementation of pharmacist's recommendations by doctors was 73.5% (200/272) (95% CI 67.9 – 78.7%;P < 0.001). The response rate of doctors was higher at the post-intervention period (92.3%; 12/13) compared to the baseline (66.7%; 8/12). At the post-intervention survey 91.6% of doctors were happy to work with competent clinical pharmacists and accepted the necessity of this service to improve standards of care. The nurses' rate of response at baseline and post-intervention surveys were 80.0 and 0.0% respectively. Their perceptions on the role of clinical pharmacist were negative at baseline survey. Conclusions There was high acceptance and implementation of clinical pharmacist's recommendations regarding DRPs by the healthcare team. The doctors' views and attitudes were positive regarding the inclusion of a ward-based pharmacist to the healthcare team. However there is a need to improve liaison between clinical pharmacist and nursing staff. Trial registration Sri Lanka Clinical Trials RegistrySLCTR/2013/029 Date: 13 September 2013; retrospectively registered.